Propuesta de mejora bajo la estandarización de procesos de producción en la reconstructora de motores j. Herrera SAS (2024)
This degree project aims to improve the productivity of the engine rebuilder J. Herrera SAS by standardizing production processes. The company, dedicated to the repair of gas, diesel and gasoline engines, faces problems such as an inefficient plant layout and a lack of adequate control of delivery times, which generates delays and low customer satisfaction.